2017
DOI: 10.1136/bmjopen-2017-017358
|View full text |Cite
|
Sign up to set email alerts
|

Failures to further developing orphan medicinal products after designation granted in Europe: an analysis of marketing authorisation failures and abandoned drugs

Abstract: ObjectivesThe research and development process in the field of rare diseases is characterised by many well-known difficulties, and a large percentage of orphan medicinal products do not reach the marketing approval.This work aims at identifying orphan medicinal products that failed the developmental process and investigating reasons for and possible factors influencing failures.DesignDrugs designated in Europe under Regulation (European Commission) 141/2000 in the period 2000–2012 were investigated in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Less than 50% of cancer drugs with orphan designation by the FDA received such status in the EMA. Our results are consistent with other studies showing that the USA has more orphan drug designations in general and specifically for oncology drugs compared with the EU 21 27 28. Drugs that targeted biomarker-defined subsets of common cancer types often received orphan status in the USA, but did not get similar status in the EU.…”
Section: Discussionsupporting
confidence: 91%
“…Less than 50% of cancer drugs with orphan designation by the FDA received such status in the EMA. Our results are consistent with other studies showing that the USA has more orphan drug designations in general and specifically for oncology drugs compared with the EU 21 27 28. Drugs that targeted biomarker-defined subsets of common cancer types often received orphan status in the USA, but did not get similar status in the EU.…”
Section: Discussionsupporting
confidence: 91%
“…Even more, when we look at the last 5 years (2011-15), the proportion of treatments that proceed to market is even more discouraging, and only 4,4% (18 drugs) of those positive opinions are marketed (range 0-12%). In an analysis of the first decade of approvals by EMA (2000-2012), Giannuzzi [16] showed that a large number of drugs never started development (abandoned drugs) whereas for those there was a development 47% reached phase III, but still point to bankruptcy as the second cause for discontinuation of approval process, possibly linked to their small size and financial capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of explanatory variables was based on the analysis of previous studies. [17][18][19] The number of patients, availability of alternative treatment, company size of the applicant (3000ࣚ or <3000 employees), nationality of the applicant, experience with orphan drug development in Japan, new molecular entity, and Anatomical Therapeutic Chemical classification were used as explanatory variables. Drugs under the Anatomical Therapeutic Chemical classification B, C, D, G, H, M, P, R, S, and V, each of which comprised <10% of the total data set, were grouped together in logistic regression.…”
Section: Methodsmentioning
confidence: 99%